Effective photocatalytic activity of mixed Ni/Fe-base metal-organic framework under a compact fluorescent daylight lamp - Vo, Dai-Viet N.; Nguyen, Vinh Huu; Nguyen, Trinh Duy; Bach, Long Giang; Hoang, Thai; Bui, Quynh Thi Phuong; Tran, Lam Dai; Nguyen, Chuong V.; Do, Sy Trung (MDPI, 2018)
Mixed Ni/Fe-base metal-organic framework (Ni/Fe-MOF) with different molar ratios of Ni 2+ /Fe 3+ have been successfully produced using an appropriate solvothermal router. Physicochemical properties of all samples were characterized using X-ray diffraction (XRD), Raman, field emission scanning electron microscopes (FE-SEM), fourier-transform infrared spectroscopy (FT-IR), N 2 adsorption-desorption analysis, X-ray photoelectron spectroscopy (XPS), ultraviolet-visible diffuse reflectance spectra (UV-Vis DRS), and photoluminescence spectra (PL). The photocatalytic degradation performances of the photocatalysts were evaluated in the decomposition of rhodamine B (RhB) under a compact fluorescent daylight lamp. From XRD, IR, XPS, and Raman results, with the presence of mixed ion Fe 3+ and Ni 2+ , MIL-88B (MIL standing for Materials of Institut Lavoisier) crystals based on the mixed metal Fe 2 NiO cluster were formed, while MIL-53(Fe) was formed with the presence of single ion Fe 3+ . From UV-Vis DRS results, Ni/Fe-MOF samples exhibited the absorption spectrum up to the visible region, and then they showed the high photocatalytic activity under visible light irradiation. A Ni/Fe-MOF sample with a Ni 2+ /Fe 3+ molar ratio of 0.3 showed the highest photocatalytic degradation capacity of RhB, superior to that of the MIL-53(Fe) sample. The obtained result could be explained as a consequence of the large surface area with large pore volumes and pore size by the Ni 2+ incorporating into the MOF’s structure. In addition, a mixed metal Fe/Ni-based framework consisted of mixed-metal cluster Fe 2 NiO with an electron transfer effect and may enhance the photocatalytic performance.